2013
DOI: 10.1152/japplphysiol.00970.2013
|View full text |Cite
|
Sign up to set email alerts
|

Brain stem serotonin protects blood pressure in neonatal rats exposed to episodic anoxia

Abstract: In neonatal rodents, a loss of brain stem serotonin [5-hydroxytryptamine (5-HT)] in utero or at birth compromises anoxia-induced gasping and the recovery of heart rate (HR) and breathing with reoxygenation (i.e., autoresuscitation). How mean arterial pressure (MAP) is influenced after an acute loss of brain stem 5-HT content is unknown. We hypothesized that a loss of 5-HT for ∼1 day would compromise MAP during episodic anoxia. We injected 6-fluorotryptophan (20 mg/kg ip) into rat pups (postnatal days 9-10 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…It is also possible that the inducible, acute neuronal perturbation approach offers greater sensitivity and thus capacity to uncover more extensive phenotypes: as applied here, it allowed each animal to serve as its own control, enabling within-animal comparisons across pre- versus during-perturbation measurements, minimizing between-animal variability. An additional benefit of the inducible-perturbation approach is that body weight variation among pups was negligible, lessening technical variability associated with acquiring plethysmographic measurements on especially small pups; by contrast, chronic developmental perturbations of Pet1 neurons results in impaired growth and diminished body weight ( Barrett et al, 2016 ; Cummings et al, 2011a ; Cummings et al, 2013 ; Erickson et al, 2007 ; Pelosi et al, 2014 ; Yang and Cummings, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the inducible, acute neuronal perturbation approach offers greater sensitivity and thus capacity to uncover more extensive phenotypes: as applied here, it allowed each animal to serve as its own control, enabling within-animal comparisons across pre- versus during-perturbation measurements, minimizing between-animal variability. An additional benefit of the inducible-perturbation approach is that body weight variation among pups was negligible, lessening technical variability associated with acquiring plethysmographic measurements on especially small pups; by contrast, chronic developmental perturbations of Pet1 neurons results in impaired growth and diminished body weight ( Barrett et al, 2016 ; Cummings et al, 2011a ; Cummings et al, 2013 ; Erickson et al, 2007 ; Pelosi et al, 2014 ; Yang and Cummings, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet evidence for an acute, real-time role for postneonatal serotonergic neurons in modulation of the autoresuscitation response remains lacking. Studies have largely involved chronic or extended 5-HT system manipulations spanning embryonic ( Barrett et al, 2016 ; Chen et al, 2013 ; Cummings et al, 2011a ; Erickson and Sposato, 2009 ) and/or postneonatal development ( Yang and Cummings, 2013 ) in which secondary, compensatory network changes can occur in addition to the primary, engineered serotonergic neuronal abnormality. Here we report progress in this area through studies in which we acutely induced Pet1 -neuron perturbation in vivo at P8 and measured cardiorespiratory outcome and recovery across a chain of asphyxic-induced apneas.…”
Section: Introductionmentioning
confidence: 99%
“…In acute 5‐HT depleted rat pups, Yang et al . showed that a progressive and premature deterioration of blood pressure is associated with delayed HR recovery with successive episodes of anoxia despite normal gasping (Yang & Cummings, ), suggesting 5‐HT deficiency can also lead to an autonomic imbalance and impair autoresuscitation process.…”
Section: Discussionmentioning
confidence: 99%
“…Gene polymorphisms related to serotonergic autonomic system may play a role in SIDS (24). In a recent study in neonatal rodents, loss of brain stem 5HT may explain the cardiovascular collapse during apparent severe hypoxic event in some SIDS cases (25). Recent neuropathology studies in SIDS implicate defective neurotransmitter function in the medullary arcuate nucleus, receptor immaturity of the “respiratory center” nucleus tractus solitarius (NTS), and defective function of the serotonergic raphé nuclei of the ponto-medullary ventral median septum and other brainstem serotonergic neurons (26).…”
Section: Introductionmentioning
confidence: 99%